Normal Values for Mesopic and Photopic Contrast Sensitivity Function with and without Glare using a Sinusoidal Bull's-Eye Target. - Harris, Paul A.; German, Zachary; Roberts, Laurel (Optometry & Visual Performance, 2019)
Purpose: To determine the normal mesopic and photopic contrast sensitivity function in young, healthy individuals with a sinusoidal bull's-eye with and without glare. Methods: Contrast sensitivity (CS) was measured on 105 healthy volunteers with 20/20 BCVA. A sinusoidal bull's-eye target was used for all tests. After dark adaptation, four different spatial frequencies under mesopic and five different spatial frequencies under photopic conditions were presented in a two-choice, forced-choice paradigm. Each of the nine conditions was tested under three different levels of glare and without glare. The targets were varied in each trial from high contrast to threshold using a staircase method. Results: The without-glare condition demonstrated the expected CS curve; each of the different glare conditions dropped CS statistically significantly. Low- and medium-glare levels dropped CS by similar amounts, showing a 0.1 log (NOTE: all log units in this paper are log10) decrease under both conditions. The high-glare condition dropped the CS by greater than an additional 0.1 log compared with the low and medium conditions. Standard deviations were small in each condition tested, which leads to the conclusion that in this group of 105 healthy subjects, the differences seen from condition to condition are demonstrable. Conclusion: Glare testing, combined with the sinusoidal bull's-eye target, may become a valuable clinical and research tool to aid in the diagnosis of visual conditions affecting the CSF, as well as for measuring the effects of optical and medical interventions on visual performance.